ANALISIS DESKRIPTIF QUARTER-LIFE CRISIS PADA LULUSAN PERGURUAN TINGGI UNIVERSITAS KATOLIK MUSI CHARITAS - Agustinus Riyanto; Diana Putri Arini (JURNAL PSIKOLOGI MALAHAYATI, 2021)
ABSTRACT: QUARTER-LIFE CRISIS DESCRIPTVE ANALYSIS ON COLLEGE GRADUATES OF KATOLIK MUSI CHARITAS UNIVERSITY Quarter-life crisis is a phenomenon of anxiety over the age of 20, which is the transition from late adolescence to adulthood. The research objective was to reveal the quarter-life crisis phenomenon in freshmen graduates. Research participants were 115 graduate students for the 2019 and 2020 periods from the  Catholic University of Musi Charitas. The analysis technique used is statistical description analysis, data collection using a quarter-life crisis scale which is given online using WhatsApp Group. Based on the research results, it was found that 86% of students experienced a quarter-life crisis. Based on the results of interviews, the anxiety experienced by students was related to careers which were considered difficult to find suitable jobs and feelings of being trapped with jobs because of financial needs. This research is a preliminary study to analyze the quarter-life crisis. It is hoped that this research can be continued to look at various other variables that are thought to have contributed to the quarter-life crisis. Keywords: quarter-life crisis, anxiety, college graduates Quarter-life crisis adalah fenomena kecemasan di usia 20 tahun keatas yang merupakan transisi masa remaja akhir menuju masa dewasa muda. Tujuan penelitian adalah mengungkap fenomena quarter-life crisis pada mahasiswa baru lulus. Partisipan penelitian adalah 115 mahasiswa lulusan periode 2019 dan 2020 dari Universitas Katolik Musi Charitas. Teknik Analisis yang digunakan adalah analisis deskripsi statistika, pengumpulan data menggunakan skala quarter-life crisis yang diberikan secara daring menggunakan whatsapp group. Berdasarkan hasil penelitian ditemukan ada 86% mahasiswa yang mengalami quarter-life crisis. Berdasarkan hasil wawancara, kecemasan yang dialami mahasiswa berhubungan dengan karir yang dianggap sulit untuk mencari pekerjaan yang sesuai dan perasaan terjebak dengan pekerjaan karena kebutuhan finansial. Penelitian ini merupakan penelitian awal untuk menganalisa quarter-life crisis, harapannya penelitian ini dapat diteruskan untuk melihat berbagai variabel lain yang diduga berkontribusi terhadap quarter-life crisis. Kata kunci : quarterlife-crisis, kecemasan, lulusan perguruan tinggi